A Conservation Management Plan for Gordion and its Environs. (November 2013) - Erder, Evin H.; Gürsan-Salzmann, Ays¸e; Miller, Naomi F.
<x content-type="archive" xml:space="preserve">Abstract</x> A Conservation Management Plan for Gordion and its Environs has been developed by a multidisciplinary team within a partnership between the University of Pennsylvania (both the School of Design and Museum of Archaeology and Anthropology) and Middle East Technical University (Faculty of Architecture) in Ankara. The project has involved a new approach to the protection of cultural material at the site itself, as well as the survey and documentation of a 140 km2 area, with Gordion as its centre, to include the village of Yassıhöyük and five nearby villages, historic sites, höyüks, or settlement mounds, and tumuli, or burial mounds. The project utilized photographs and standardized forms in the documentation of public and private buildings and areas. Based on this survey, the values of the site and its environs were reassessed, and an action plan presented for all project stakeholders. One of the primary stakeholders is the local population, who must be made aware of the damaging effects of deep ploughing to the tumuli.